Electronic word of mouth, price, store atmosphere, and brand image on food purchasing decisions - Gede Feby Suarjaya Putra (Review of Management, Accounting, and Business Studies, 2025)
This research aims to the culinary business is an activity of producing F&B that aims to be sold to consumers in the hope of getting the maximum possible profit. Kober Mie Setan Branch of Dewi Sri is a well-known culinary business in Bali. Instagram is used by Kober Mie Setan, Dewi Sri Branch to promote the products it sells using the electronic word- of-mouth method. Communication via the internet was carried out by Kober Mie Setan, Dewi Sri Branch, to discuss product issues, one of which was price. Prices are inseparable from the store atmosphere. Mie Setan Kober created a new slogan, namely "Founders are not imitators". This creates a new brand image that is different in the minds of consumers. Consumers consider existing factors before buying a product in different ways according to generations. The purpose of this study was to determine the effect of electronic word of mouth, price, store atmosphere, and brand image on food purchasing decisions partially at the research location of Kober Mie Setan, Dewi Sri Branch. The population in this study are Generation Z consumers of Kober Mie Setan, Dewi Sri Branch. The number of samples in this study was determined using the Hair et al formula, so 125 respondents were obtained with the provisions of the sample criteria for this study. The research hypothesis was tested with the SmartPLS application. The results of this study indicate that the variables electronic word of mouth, store atmosphere, and brand image partially have a positive and significant effect on purchasing decisions and price has no effect on purchasing decisions.